Figurative Language in the Song Lyrics of 5 Seconds of Summerand One Direction’s Albums - Dina Sinjiardita, Ni Putu; Tika, I Ketut (Humanis; Vol 22 No 3 (2018)DO - 10.24843/JH.2018.v22.i03.p18, 2018)
Abstra ct This study is entitled Figurative Language in The Song Lyrics of 5 Seconds of Summer and One Direction’s Albums. This study is aimed to identify figurative language and explain the meaning of those types of figurative language found in the song lyrics of 5 Seconds of Summer’s album entitled “Sounds Good Feels Good” and One Direction’s album entitled “Midnight Memories”. The data were collected using the documentation research method. After the required data were collected, they were analyzed using qualitative method. The analysis of the data were presented in a descriptive way to give clear explanation. The findings show that in 5 Seconds of Summer’s album five types of figurative language found in the data; they are: personification, irony, simile, metaphor and hyperbole. While from One Direction’s album four types of figurative language were found; they are: personification, simile, metaphor and hyperbole. There were two types of meaning found in the data; they are: conceptual meaning and connotative meaning. It can be concluded that in the rock band’s album Sounds Good Feels Good irony was found; however, in pop band’s album Midnight Memories irony was not found. Both in those two albums conceptual meaning was more frequently used.